Start me up: The relationship between volcanic eruption characteristics and eruption initiation mechanisms - Kent, Adam J. R.; Till, Christy B.; Cooper, Kari M. (Volcanica, 2023)
Understanding the processes that initiate volcanic eruptions after periods of quiescence are of paramount importance to interpreting volcano monitoring signals and mitigating volcanic hazards. However, studies of eruption initiation mechanisms are rarely systematically applied to high-risk volcanoes. Studies of erupted materials provide important insight into eruption initiation, as they provide direct insight into the physical and chemical changes that occur in magma reservoirs prior to eruptions, but are also often underutilized. Petrologic and geochemical studies can also constrain the timing of processes involved in eruption initiation, and the time that might be expected to elapse between remote detection of increased activity and eventual eruption. A compilation and analysis of literature data suggests that there are statistical differences in the composition, volume, style and timescales between eruptions initiated by different mechanisms. Knowledge of the processes that initiate eruptions at a given volcano may thus have significant predictive power.